CO2 reactivity with Mg2NiH4 synthesized by in situ monitoring of mechanical milling. Issue 4 (9th January 2020) - Grasso, M. L.; Puszkiel, J.; Gennari, F. C.; Santoru, A.; Dornheim, M.; Pistidda, C.
Abstract : CO2 capture and conversion are a key research field for the transition towards an economy only based on renewable energy sources. Abstract : CO2 capture and conversion are a key research field for the transition towards an economy only based on renewable energy sources. In this regard, hydride materials are a potential option for CO2 methanation since they can provide hydrogen and act as a catalytic species. In this work, Mg2 NiH4 complex hydride is synthesized by in situ monitoring of mechanical milling under a hydrogen atmosphere from a 2MgH2 :Ni stoichiometric mixture. Temperature and pressure evolution is monitored, and the material is characterized, during milling in situ, thus providing a good insight into the synthesis process. The cubic polymorph of Mg2 NiH4 (S.G . Fm 3̄ m ) starts to be formed in the early beginning of the mechanical treatment due to the mechanical stress induced by the milling process. Then, after 25 hours of milling, Mg2 NiH4 with a monoclinic (S.G. C 12/ c 1) structure appears. The formation of the monoclinic polymorph is most likely related to the stress release that follows the continuous refinement of the material's microstructure. At the end of the milling process, after 60 hours, the as-milled material is composed of 90.8 wt% cubic Mg2 NiH4, 5.7 wt% monoclinic Mg2 NiH4, and 3.5 wt% remnant Ni. The as-milled Mg2 NiH4 shows high reactivity for CO2 conversion into CH4 . Under static conditions at 400 °C for 5 hours, the interactions between as-milled Mg2 NiH4 and CO2 result in total CO2 consumption and in the formation of the catalytic system Ni–MgNi2 –Mg2 Ni/MgO. Experimental evidence and thermodynamic equilibrium calculations suggest that the global methanation mechanism takes place through the adsorption of C and the direct solid gasification towards CH4 formation.